Aerobic fitness and technical efficiency at high intensity discriminate between elite and subelite tennis players - Baiget, E.; Iglesias, X.; Rodriguez, F. A. (International Journal of Sports Medicine, 2016)
The aim of this study was to determine whether selected physiological, performance and technical parameters derived from an on-court test are capable of discriminating between tennis players of national and international levels. 38 elite and subelite tennis players were divided into international level (INT, n=8) and national level players (NAT, n=30). They all performed a specific endurance field test, and selected physiological (maximum oxygen uptake [VO2max], and ventilatory thresholds [VT1 and VT2]), performance (test duration, final stage and hits per test) and technical (technical effectiveness [TE]) parameters were compared. INT showed greater VO2max, VO2 at VT2 (ml·kg-1·min-1), test duration (s), final stage (no.), hits per test (no.) and TE (% of successful hits), as compared with NAT (p<0.05). At high exercise intensity (stages 5 and 6), the INT achieved better TE than NAT (p=0.001-0.004), and the discriminant analyses showed that these technical parameters were the most discriminating factors. These results suggest that this specific endurance field test is capable of discriminating between tennis players at national and international levels, and that the better aerobic condition of the INT is associated with better technical efficiency at higher exercise intensities.